Sodium signal intensity of CSF using 1H-guided 23Na-MRI as a potential noninvasive biomarker in Alzheimer's disease: clinical investigative study - Kerl, Hans Ulrich; Baazaoui, Hakim; Herrmann, Katrin Elisabeth; Adlung, Anne; Ludwig, Nadia K.; Hausner, Lucrezia; Frölich, Lutz; Schad, Lothar R.; Groden, Christoph; Mohamed, Sherif A. (Journal of neuroimaging, 2024)
Background and Purpose Alzheimer's disease (AD) is characterized by cognitive decline and mnestic deficits. The pathophysiology of AD is not fully understood, which renders the development of accurate tools for early diagnosis and effective therapies exceedingly difficult. In this study, we investigated the use of 23Na-MRI to measure the relative sodium signal intensities (rSSIs) in CSF in patients with AD and healthy controls. Methods We prospectively recruited 11 patients with biomarker-diagnosed early-stage AD, as well as 12 cognitively healthy age-matched controls. All participants underwent 23Na-MRI to measure rSSI. Statistical analyses were performed to compare CSF sodium signal intensities between groups and to evaluate the specificity and sensitivity of the rSSI in the diagnosis of AD. Results RSSIs in CSF were significantly higher in AD patients (mean = 68.6% ± 7.7%) compared to healthy controls (mean = 56.9% ± 5.5%) (p < .001). There was also a significant negative correlation between rSSI in CSF and hippocampus and amygdala volumes (r = −.54 and −.49, p < .05) as well as a positive correlation with total CSF volumes (r = .81, p < .05). Receiver operating characteristic analysis showed high diagnostic accuracy for rSSI in discriminating between AD patients and healthy controls (area under the curve = .94). Conclusion Our study provides evidence that rSSI in CSF is increased in AD patients in comparison to healthy controls. rSSI may serve as a potential marker for early detection and monitoring of disease progression. Larger, longitudinal studies are needed to confirm our findings and to investigate the association between rSSI in CSF and the severity of cognitive impairment.
Erstmals veröffentlicht: 28. Mai 2024
Gesehen am 10.12.2024